Effect of Financial Inclusion on Multidimensional Poverty in Togo - Atchi, Kokou Fambari (DEMO, 2022)
This article examines the effect of financial inclusion on poverty from the perspective of the multidimensional deprivations of individuals in Togo. Using data extracted from the Finscope survey database, an instrumental variable probit model is used for econometric estimations. The results show that a 1% increase in the probability of financial inclusion is associated with a 3.5% decrease in the multidimensional poverty index (MPI) in Togo. The effect is more pronounced in women and in individuals living in urban areas. Government investment and financial sector regulation will be a necessary step to strengthen financial inclusion in Togo.(original abstract)